A Whole Systems Approach to Hospital Waste Management in Rural Uganda - Kwikiriza, Stuart; Stewart, Alex G.; Mutahunga, Birungi; Dobson, Andrew E.; Wilkinson, Ewan (Frontiers in Public Health, 2019)
Introduction: Safe waste management protects hospital staff, the public, and the local environment. The handling of hospital waste in Bwindi Community Hospital did not appear to conform to the hospital waste management plan, exhibiting poor waste segregation, transportation, storage, and disposal which could lead to environmental and occupational risks. Methods: We undertook a mixed-methods study. We used semi-structured interviews to assess the awareness of clinical and non-clinical staff of waste types, risks, good practice, and concerns about hospital waste management. We quantified waste production by five departments for 1 month. We assessed the standard of practice in segregation, onsite transportation, use of personal protective equipment, onsite storage of solid waste, and disposal of compostable waste and chemicals. Results: Clinical staff had good awareness of waste (types, risk) overall, but the knowledge of non-clinical staff was much poorer. There was a general lack of insight into correct personal or departmental practice, resulting in incorrect segregation of clinical and compostable waste at source (>93% of time), and incorrect onsite transportation (94% of time). In 1 month the five departments produced 5,398 kg of hazardous and non-hazardous waste (12; 88%, respectively). Good practice included the correct use of sharps and vial boxes and keeping the clinical area clear of litter (90% of the time); placentae buried immediately (>80% of the time); gloves were worn everyday by waste handlers, but correct heavy-duty gloves <33% of the time, reflecting the variable use of other personal protective equipment. Chemical waste drained to underground soakaways, but tracking further disposal was not possible. Correct segregation of clinical and compostable waste at source, and correct onsite transportation, only occurred 6% of the time. Conclusion: Waste management was generally below the required WHO standards. This exposes people and the wider environment, including the nearby world heritage site, home to the endangered mountain gorilla, to unnecessary risks. It is likely that the same is true in similar situations elsewhere. Precautions, protection, and dynamic policy making should be prioritized in these hospital settings and developing countries.